The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10750-007-0740-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of water depth and sediment type on clonal growth of the submersed macrophyte Vallisneria natans

Abstract: The response of clonal growth and ramet morphology to water depth (from 60 to 260 cm) and sediment type (sand versus organic clay) was investigated for the stoloniferous submersed macrophyte Vallisneria natans in an outdoor pond experiment. Results showed that water depth significantly affected clonal growth of V. natans in terms of clone weight, number of ramets, number of generations, clonal radius and stolon length. V. natans showed an optimal clonal growth at water depths of 110-160 cm, but at greater dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…The results obtained here also indicate that V. natans has wide ecological amplitude to nutrient availability in sediment. Xiao et al (2007) has indicated that water depth and sediment type have differential effects on the growth of V. natans. Water depth affects its clonal growth significantly except for clonal weight, which is significantly affected by sediment type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained here also indicate that V. natans has wide ecological amplitude to nutrient availability in sediment. Xiao et al (2007) has indicated that water depth and sediment type have differential effects on the growth of V. natans. Water depth affects its clonal growth significantly except for clonal weight, which is significantly affected by sediment type.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that, for many submerged plants, the achievement of maximum summer biomass is impacted by both water depth and sediment composition (Chambers & Kalff 1987). The clonal growth of submerged plants is also impacted by both water depth and sediment type (Xiao et al 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus MDA is often used as stress resistance indicators for environmental stresses (Li 2000). To understand the mechanisms that lead to the loss of macrophytes, we used the submerged macrophyte V. natans, an ecologically important species widely used in nutrient removal in eutrophic waters, because rapid decline of V. natans is observed with eutrophication of lakes (Xiao et al 2007). We investigated the responses of chlorophyll content and MDA levels, as indicators of physiological responses, to common environmental stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we focused on the combined effects of the two main toxins, dissolved ammonia and dissolved MC-LR that arise as a result of cyanobacterial bloom decay, a process that seriously impact fresh waters. In the experiments, therefore, we used submerged macrophyte Vallisnerria natans, an ecologically important species widely used in nutrient removal in eutrophic waters (Xiao et al 2007), as a test aquatic plant to determine the antioxidant responses to the combined toxicity of microcystin and ammonia. We hypothesized that:…”
mentioning
confidence: 99%